Increasing Interest in Learning Islamic Religious Education Through A Problem Based Learning Model Assisted By Audio Visual Media - Hasno Handoko; Andra, Devi (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2023)
This study aims to improve the learning interest of second-grade elementary students in the topic of the story of Prophet Nuh (A.S.) within Islamic Religious Education through the use of audio-visual media in the form of video. The research was conducted at an elementary school in Natuna Regency using a Classroom Action Research approach implemented in two cycles. The participants were second-grade students enrolled in Islamic Religious Education classes. Data were collected through classroom observations of students' learning interest and participation, as well as questionnaires administered at the end of each cycle. The data were analyzed using descriptive quantitative techniques supported by qualitative reflective analysis to identify changes in students' learning interest throughout the intervention. The findings indicate a consistent improvement in students' learning interest across the cycles, as reflected in increased attention, engagement, and active participation during the learning process. The use of audio-visual media enabled the prophetic narrative to be presented in a more concrete and engaging manner, which aligned with the learning characteristics of elementary school students. Pedagogically, this study provides empirical evidence that integrating audio-visual media into Islamic Religious Education can effectively enhance students' learning interest in narrative-based religious content and offers an innovative instructional strategy for improving the quality of Islamic education at the elementary level.